INSTINCT: a flow-based open-source PNT framework for satellite navigation and sensor fusion - Thomas Topp; Marcel Maier; Thomas Hobiger; Doris Becker (GPS Solutions, 2025)
INS toolkit for integrated navigation concepts and training (INSTINCT) is an open-source positioning, navigation and timing (PNT) framework for global navigation satellite system (GNSS) navigation and sensor fusion written in C++. It uses flow-based programming to encapsulate functionality, enforce clean interfaces and promote reusability. Not only multi-constellation, multi-frequency single point positioning (SPP) and real-time kinematic positioning (RTK) algorithms are available, but also inertial navigation system (INS)/GNSS sensor fusion. Moreover, innovative concepts like multi inertial measurement unit (IMU) arrays and factor graph optimization are featured. Furthermore, most file formats common in the PNT field can be read with the software and converted between them. Also, simulation of trajectories and IMU data with different error models is possible. A graphical user interface allows the user to directly set parameters and analyze results in plots, which enables rapid prototyping and testing. A developer can easily extend the functionality with own algorithms and sensor interfaces building upon the existing modules. In order to evaluate the performance of the algorithms two experiments were performed. Analysis of a static dataset shows that the position accuracy of the RTK algorithm of INSTINCT is comparable to RTKLIB. Additionally, a dynamic dataset was generated using a Spirent GNSS simulator and INSTINCT’s IMU simulation capabilities. In-depth assessment confirms the high accuracy of the results and demonstrates that the INS/GNSS loosely coupled Kalman filter can compensate for GNSS outages.

Validation of a method to determine transformation of chemicals in anaerobic liquid pig and cattle manure for the OECD test guideline programme - Silvia Berkner; Julia Margaretha Anke; Rolf-Alexander Düring; Silke Fiebig; Thomas Junker; Dieter Hennecke; Monika Herrchen; Maria Meinerling; Jörg Römbke; Sören Thiele-Bruhn; Edward Topp; Wolfgang Völkel; et al. (Chemosphere, 2023)

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.